2021
DOI: 10.1177/14653125211006113
|View full text |Cite
|
Sign up to set email alerts
|

Is orthodontic treatment associated with changes in self-esteem during adolescence? A longitudinal study

Abstract: Objective: This study explored the association between history of orthodontic treatment and changes in self-esteem among British adolescents. Design: Birth cohort study. Setting: United Kingdom. Participants: Data from 2600 participants of the British Cohort Study were analysed. Methods: Participants completed the Lawrence Self-Esteem Questionnaire (LAWSEQ) at the ages of 10 and 16 years. The change in LAWSEQ score over six years was the outcome. Participants were divided into two groups according to parental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…These findings are in accordance with other studies whose findings led to the conclusion that an improvement in self-esteem is among the most noteworthy outcomes of orthodontic treatment [ 6 ] and that enhanced physical attractiveness resulting from orthodontic treatment positively impacts self-esteem [ 17 ]. However, some studies did not provide evidence that there is a connection between orthodontic treatment and changes in self-esteem during adolescence [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…These findings are in accordance with other studies whose findings led to the conclusion that an improvement in self-esteem is among the most noteworthy outcomes of orthodontic treatment [ 6 ] and that enhanced physical attractiveness resulting from orthodontic treatment positively impacts self-esteem [ 17 ]. However, some studies did not provide evidence that there is a connection between orthodontic treatment and changes in self-esteem during adolescence [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Orthodontic treatment (OT) is commonly performed in children, adolescents, and adults for the improvement of dentofacial esthetics, oral function, and occlusion. 22 23 Since OT and LC are prevalent in the general population (including both growing patients and adults), it is reasonable to assume that a growing number of individuals with LC are currently undergoing or will undergo OT. It has been reported that patients who experience mild or even asymptomatic COVID-19 infection exhibit a prolonged inflammatory and stress response even after 40 days postinfection.…”
Section: Lc In Orthodontic Populationsmentioning
confidence: 99%
“…The goal of orthodontic therapy is to rectify malocclusion, which is gaining popularity since it can enhance masticatory function, dental aesthetics, psychological and social wellness, and overall and oral health. 1 In addition to its advantages, orthodontic treatment carries some dangers and consequences, just like any other kind of medical care.…”
Section: Introductionmentioning
confidence: 99%